Predictors of cerebrovascular events at mid-term after transcatheter aortic valve implantation – Results from EVERY-TAVI registry. (1st October 2017) - Jochheim, David; Zadrozny, Magda; Ricard, Ingrid; Sadry, Tobias Mir; Theiss, Hans; Baquet, Moritz; Schwarz, Florian; Bauer, Axel; Khandoga, Alexander; Sadoni, Sebastian; Pichlmaier, Maximilian; Hausleiter, Joerg; et al.
Abstract: Background: Clinical relevant cerebrovascular events (CVE) following transcatheter aortic valve implantation (TAVI) still remain a devastating complication associated with mortality and severe impairments. Therefore, identification of particularly modifiable predictors of this complication is clinically relevant and an important step for planning preventive strategies. Methods: A total of 985 patients who underwent trans-femoral TAVI for aortic valve stenosis in our institution from February 2008 to January 2015 were considered. The influence of demographics, clinical and procedural data on the occurrence of CVE was assessed with a competing risk model with death as competing event. Clinical events were defined according to VARC-2 criteria. Results: At a median follow-up of 838 days, 95% CI 807–892, 59 patients experienced any CVE (5.9%) and the overall cumulative mortality rate was 46.1%. CVEs mainly occur later than 30 days after TAVI (47.5%), 88.1% of them were of ischemic origin and 52.5% were disabling events. Independent predictors of CVEs were age (hazard ratio 1.05; 95% CI 1.01 to 1.09), history of CVE (hazard ratio 2.54; 95% CI 1.39 to 4.63) and use of balloon post-dilation (hazard ratio 1.85; 95% CI 1.08 to 3.18). Conclusion: In patients undergoing TAVI incidence of clinically relevant CVEs is frequent with half of the events occurring after the first 30 days post-TAVI. Identification of balloon post-dilation as the only modifiable predictor of CVE risk at mid-term, urges its cautious performance after prosthesis implantation. ClinicalTrials.gov identifier: NCT02289339.